2020
DOI: 10.3389/fpsyt.2020.00861
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Day Acceptance and Commitment Therapy (ACT) Workshop Increases Presence and Work Functioning in Healthcare Workers

Abstract: Background In this controlled naturalistic study performed in healthcare workers we examined the effect of a two-day acceptance commitment therapy (ACT) workshop on work presence and productivity, i.e. the influence the workshop had on treatment efficacy in a routine hospital care setting. Aim To examine the influence of ACT on productivity and presence in healthcare workers. Method Study participants were all healthcare workers (nurses, medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…A number of interventions focused on cognitive, behavioral, and social processes have been applied to the treatment of moral injury in warzone Veterans and Service-Members which may be relevant to helping healthcare providers respond to moral distress more flexibly [28][29][30]. Interventions, such as Acceptance and Commitment Therapy, which have been developed to target both psychosocial functioning in moral injury [27,28] and psychosocial functioning within healthcare providers [31,32], may be particularly beneficial.…”
Section: Plos Onementioning
confidence: 99%
“…A number of interventions focused on cognitive, behavioral, and social processes have been applied to the treatment of moral injury in warzone Veterans and Service-Members which may be relevant to helping healthcare providers respond to moral distress more flexibly [28][29][30]. Interventions, such as Acceptance and Commitment Therapy, which have been developed to target both psychosocial functioning in moral injury [27,28] and psychosocial functioning within healthcare providers [31,32], may be particularly beneficial.…”
Section: Plos Onementioning
confidence: 99%
“…Thus, there were 41 studies included at this stage. At the final level of review for inclusion, 13 additional studies were excluded because the meditation component was mixed with other types of interventions (D’Amico et al, 2020 ; Doyle et al, 2019 ; Gaupp et al, 2020 ; Ljótsson et al, 2011 , 2014 ; Mercer et al, 2016 ; Orme-Johnson & Herron, 1997 ; Stahl et al, 2015 ; Sun et al, 2021 ), they were feasibility studies with only intervention costs (Hennelly et al, 2020 ; Tulloh et al, 2018 ), the effectiveness outcome included for cost-effectiveness calculation was not a health-related outcome (e.g., teaching competency as the effectiveness outcome; Crane et al, 2020 ), or the meditation intervention was not an MBI (Herron, 2011 ), leaving 28 studies meeting the criteria to be included in this study (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Scholars have consistently found support for ACT offered to health care professionals in 1- or 2-day workshops. Gaupp and colleagues (2020) demonstrated that a 2-day ACT workshop delivered to registered nurses and nursing assistants employed in a psychiatric setting improved patient scores on a clinician-rated measure of function and reduced workplace absences. Waters et al (2018) similarly determined that a 1-day ACT workshop resulted in lower self-reported scores on measures of psychological distress and cognitive fusion and higher scores on questionnaires assessing mindfulness and psychological flexibility at a 3-month follow up.…”
Section: Acceptance and Commitment Therapy/trainingmentioning
confidence: 99%
“…Patient surveys assessing experience of care, patient readmission rates, and 30-day mortality postdischarge might already be tracked by health care systems (Kelley & Gravina, 2017) and can be used to examine potential benefits. Data on employee retention and sick leave utilization (Gaupp et al, 2020) may provide information on health care professional well-being. Broader system data can be supplemented with targeted observation of key outcomes, such as adherence to safety procedures (Gravina et al, 2021) gathered via behavioral observation.…”
Section: Measuring Outcomesmentioning
confidence: 99%